Implementation of quasiclassical mapping approaches for nonadiabatic molecular dynamics in the PySurf package - Picconi, David; Menger, Maximilian; Palacino-González, Elisa; Salazar, Edison X.; Faraji, Shirin (Physical chemistry, chemical physics, 2025)
Quasiclassical methods for nonadiabatic molecular dynamics, based on Mayer-Miller-Stock-Thoss mapping, are implemented in the open source computer package PySurf. This complements the implementation of surface hopping approaches performed in previous studies, and leads to a unified code that allows nonadiabatic dynamics simulations using various mapping approaches (Ehrenfest dynamics, the linearised semiclassical initial value representation, the Poisson-bracket mapping equation, the “unity” approach for the identity operator, the spin mapping, and the symmetrical quasiclassical windowing method) as well as different flavours of surface hopping (fewest-switches, Landau-Zener, and a mapping-inspired scheme). Furthermore, a plugin is developed to provide diabatic vibronic models as input in a sum-of-products form. This opens the way to the benchmark of different types of trajectory-based propagators on different models, against exact quantum dynamical simulations performed, e.g., by the multiconfigurational time-dependent Hartree method. Illustrative calculations, performed using the whole set of available propagators, are presented for different harmonic and anharmonic two-state models, exhibiting various degrees of correlation between vibrational modes.